Coexistence of Myeloma and Leismaniasis in a dog - ΠΑΠΑΧΑΡΙΣΗΣ Γ.; ΔΟΝΟΣ Α.; ΜΑΝΗΣ Η.; ΣΑΡΡΗ - ΠΑΠΑΘΕΟΔΩΡΟΥ Χ. (Journal of the Hellenic Veterinary Medical Society, 2019)
Examining a dog-case of Leismaniasis in the area of Epirus it was also diagnosed Myeloma. Both diseases have common characteristics but also big variations. The coexistence in the certain case could be considered as a "coincidence" because other cases of leismaniasis were negative for Myeloma. Leismaniasis is diagnosed for first time in the area of Epirus and requires futher study